Molecular characterization and identification of economically important Potyviruses in Cucurbitaceae family from Gujranwala division of Punjab, Pakistan - Muhammad Ashfaq; Muhammad Waqas; Nadeem Ahmed; Muhammad Raheel; Hafiz Tassawar Abbas; Ashir Masroor; Rao Muhammad Ikram; Hasan Riaz; Muhammad Ishtiaq; Zulqurnain Khan; Amjad Saeed; Milan Skalicky; et al. (Journal of King Saud University: Science, 2021)
Cucurbits belongs to Cucurbitaceae family and they are main source of energy, vitamins and minerals. The plant viruses in general and potyviruses in particular are considered to hamper the successful production of cucurbits in Punjab province of Pakistan. The present study was undertaken to determine the current status of major potyviruses infecting cucurbits in Gujranwala division of Punjab. Overall, 528 samples of cucurbit species were collected from 46 fields of six districts (Narowal, Sialkot, Gujranwala, Gujrat, Mandi Baha Uddin and Hafizabad) in Gujranwala division. All disease samples were screened for the presence of potyvirus infection by indirect plate-trapped antigen (PTA)-ELISA using “Poty-group test” kit (Bioreba AG, Switzerland). These samples were further tested for Papaya ring spot virus (PRSV), Zucchini yellow mosaic virus (ZYMV) and Watermelon mosaic virus (WMV) (Bioreba AG) using virus specific DAS-ELISA. Zucchini yellow mosaic virus (ZYMV) was also further confirmed by reverse transcriptase polymerase chain reaction (RT-PCR). ZYMV was found as the most predominant virus of cucurbits in Gujranwala division with an average incidence of 20.8%, followed by PRSV (7.2%) and WMV (1.7%). Maximum mixed double infection was observed in combination of ZYMV+PRSV (1.3%) followed by ZYMV+WMV (0.4%) and WMV+PRSV (0.8%). Overall highest disease incidence of potyviruses was in Gujranwala (40.86%) followed by Narowal (34.65%), Gujrat (28.6%), Mandi Baha Uddin (26.56%), Hafizabad (25%) and Sialkot (23.21%). Likewise, the maximum ZYMV incidence was recorded in Angel Gourd whereas no viral infection was observed in snap melon and ash gourd in Gujranwala division. All cucurbits vegetables were found to be highly prone to ZYMV followed by PRSV and WMV. The sequence of CI region of ZYMV AABRM-CI ridge gourd isolate was deposited in GenBank with an accession no. MN897101, which showed nucleotide identities from 91.501-98.401% with other isolates of ZYMV available at database. Highest nucleotide identity 98.401% was found with the sequence of ZYMV South Korean isolate BR1 (MH042024) followed by 98.301% with ZYMV isolate Y23 from Turkey (KP828425). The results of the current study would be useful in devising management strategies to mitigate potyvirus losses in cucurbits from Pakistan.